Answers

The Brainliest Answer!
2015-12-25T10:44:46+05:30
1) 15 - 16yz - 15y^2z^2 let yz = x => 15 - 16x - 15x^2 = - ( 15x^2 + 16x - 15 ) = - ( 15x^2 + 25x - 9x - 15 ) = - { 5x ( 3x + 5 ) - 3 ( 3x + 5 ) } = - ( 3x+5 ) ( 5x - 3 ) = ( 3x + 5 ) ( 3 - 5x ) = ( 3yz + 5 ) ( 3 - 5yz ) __________________________________________________________________ 2) 9-a^6 + 2a^3b^3 -b^6 = - ( a^6 + b^6 - 2a^3b^3 - 9 ) = - ( a^6 - a^3b^3 + b^6 -a^3b^3 - 9 ) = - ( a^3 (a^3 - b^3 ) -b^3 ( -b^3 +a^3 ) - 9 ) = - { ( a^3 - b^3 )^2 - 9 ) = 9 - (a^3 - b^3)^2 = { 3 - (a^3 -b^3 ) } { 3 + ( a^3 - b^3) } = ( 3 -a^3 + b^3 ) ( 3 + a^3 - b^3 )
1 5 1